(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article investigates the interplay between speech acts, linguistic culture, and the theoretical foundations of linguistics. It traces the development of speech theory from early philosophical approaches to the contributions of J. L. Austin and J. R. Searle, emphasizing the classification of locutionary, illocutionary, and perlocutionary acts and their social functions. The study also explores the connection between language and culture, examining how linguistic expressions encode societal values, norms, and worldviews. Attention is given to Uzbek linguistic culture, illustrating how speech acts such as hurmat (respect), duo (blessing), and mehmondo‘stlik (hospitality) reflect ethical principles, social hierarchy, and communicative conventions. The article further discusses the implications for second-language learning and cross-cultural communication, highlighting the role of pragmatic competence in producing contextually and culturally appropriate language. Overall, the study demonstrates that speech acts are not only linguistic units, but also social actions deeply embedded in cultural frameworks, underscoring the inseparable link between language, society, and cognition.